Comparison of success rates in early stages of in vitro fertilization (IVF) in women with and without endometriosis - Haque, Arinil; Primariawan, Relly Y.; Hendarto, Hendy (Narra J, 2024)
Endometriosis remains a significant challenge for reproductive-aged women and is frequently associated with infertility. Although in vitro fertilization (IVF) is used to address infertility in women with endometriosis, its effectiveness in this context is still debated, particularly in developing countries such as Indonesia, where IVF remains a major challenge. The aim of this study was to investigate the success rates of early stages of IVF in women with and without endometriosis. A retrospective cohort study was conducted at the Graha Amerta Fertility Clinic, located within Dr. Soetomo Academic General Hospital in Surabaya, Indonesia.  The quantity and quality of oocytes (the number of oocytes obtained by ovum pick-up (OPU) and the number of metaphase II (MII) oocytes), fertilization quality (the number of two-pronuclei oocytes and fertilization rate), embryo development quality (cleavage rate and blastocyst rate), biochemical pregnancy, clinical pregnancy, and live birth rate were collected from IVF patients between 2017−2022. Independent Student’s t-test or Mann-Whitney test was used accordingly for comparison analysis. A total of 410 IVF patients were included in the study; 93 had endometriosis, while 317 had no endometriosis. Oocyte quantity obtained by OPU (p=0.016) and oocyte quality (p=0.045), as measured by the number of MII oocytes, were significantly lower in the endometriosis group compared to the non-endometriosis group. However, there were no significant differences between the two groups in terms of the number of two-pronuclei oocytes (p=0.105), fertilization rate (p=0.987), cleavage rate (p=0.467), blastocyst rate (p=0.128), biological pregnancy rates (OR: 0.98; 95%CI: 0.60–1.60; p=0.940), clinical pregnancy rate (OR: 0.69; 95%CI: 0.39–1.24, p=0.219), or live birth rate (p=0.609). These findings suggest that while endometriosis may reduce oocyte quantity and quality, it does not significantly impact the success rates of IVF.